On the numerical solutions of high order stable difference schemes for the hyperbolic multipoint nonlocal boundary value problems - Yildirim, Ozgur; Uzun, Meltem (ELSEVIER SCIENCE INC, 2015)
In this article, we consider third and fourth order of accuracy stable difference schemes for the approximate solutions of hyperbolic multipoint nonlocal boundary value problem in a Hilbert space H with self-adjoint positive definite operator A. We present stability estimates and numerical analysis for the solutions of the difference schemes using finite difference method. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Abstract hyperbolic equations; Stability; Difference equations; Nonlocal and multipoint BVPs; EQUATIONS; Mathematics